The Growth Response of Rendeu (Staurogyne elongata (Neese) Kuntze) to Shoot Pruning and Its Propagation by Shoot Cutting - Lailaty, Intani Quarta; Astutik, Sri; Surya, Muhammad Imam (Universitas Gadjah Mada, 2024)
Rendeu (Staurogyne elongata (Neese) Kuntze) is a native Indonesian plant used as food and traditional medicine in the daily life of the people residing around Gunung Halimun-Salak National Park. Due to the potential source of herbal-based medicines and traditional food in the long-run purposes, the proper method of its propagation is required, so that Rendeu can be conserved and utilised sustainably. This study employed two research designs. First, a completely randomized design with pruning and IAA (indole-3 acetic acid) treatment was used for seedling growths. Second, plant propagation applied a factorial randomized block design: planting media types and plant growth regulator (PGR) (rootone F) treatment. Observation included the number of buds, number of leaves, number of flowers, plant biomass, root length, and relative chlorophyll content using the SPAD tool. The data were analysed using ANOVA (SPSS ver. 17.0), followed by Pearson correlation analysis. The results showed that applying IAA and leaf pruning could increase the number of buds, the number of leaves and the fresh weight of S. elongata plants compared to the control plant. The addition of rootone increased the growth of Rendeu shoot cuttings, shown in all growth parameters and chlorophyll content. Humus was the best media for Rendeu’s growth among all planting medium. Planting media affected the increase in the number of leaves and the number of buds of S. elongata significantly. The interaction of planting media and PGR somewhat influenced root length and total leaf chlorophyll. The growth and production of S. elongata increased with the time of planting.